2018
DOI: 10.3390/atmos9120462
|View full text |Cite
|
Sign up to set email alerts
|

The Generation and Forecast of Extreme Winds during the Origin and Progression of the 2017 Tubbs Fire

Abstract: On 8-9 October 2017, fourteen wildfires developed rapidly during a strong Diablo wind event in northern California including the Tubbs Fire, which travelled over 19 km in 3.25 h. Here, we applied the CAWFE ® coupled numerical weather prediction-fire modeling system to investigate the airflow regime and extreme wind peaks underlying the extreme fire behavior using simulations that refine from a 10 km to a 185 m horizontal grid spacing. We found that as Diablo winds travelled south down the Sacramento Valley and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Several studies have applied CAWFE to these wind driven events to investigate the development of unrecognized extreme microscale wind phenomena and how these made fire events unfold, and the difficulty of using observations at the time to evaluate them. These reproduced key features and timing, and showed that strong winds in the Tubbs Fire [23] (Fig. 5a) occurred on secondary hilltops, rather than tall ridges, and produced pulses of strong winds exceeding 30-40 m s -1 with 4-13 minute pulses that appeared in high temporal resolution wind speed data.…”
Section: Wind-driven Megafiressupporting
confidence: 54%
See 3 more Smart Citations
“…Several studies have applied CAWFE to these wind driven events to investigate the development of unrecognized extreme microscale wind phenomena and how these made fire events unfold, and the difficulty of using observations at the time to evaluate them. These reproduced key features and timing, and showed that strong winds in the Tubbs Fire [23] (Fig. 5a) occurred on secondary hilltops, rather than tall ridges, and produced pulses of strong winds exceeding 30-40 m s -1 with 4-13 minute pulses that appeared in high temporal resolution wind speed data.…”
Section: Wind-driven Megafiressupporting
confidence: 54%
“…Studies have shown this has led to underestimates in peak wind extrema in wind-driven fire events [23], smoothed gradients across interfaces precluding WRF from producing gravity wave overturning (discussed in Coen 2018) -a primary mechanism for producing strong downslope winds driving fire events such as the 2012 High Park Fire [24] and shear instabilities [25], and smoothing gradients underlying simulation of the full development of fire phenomena such as fire whirls [20,26]. [41] and demonstrated over wildfires [42] though their broader use is still restricted.…”
Section: Computational Aspects Of Coupled Atmosphere-fire Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent, large loss wildfire event should be selected, all available data collected, and the event reconstructed in as much detail as possible using a computational fluid dynamics (CFD) model. An excellent example of reconstruction at the landscape scale for the 2017 Tubbs fire in California is given by Coen et al [67]. The goal of this grand challenge is to use meter or sub-meter scale resolution with a physics-based combustion model and a long-range spotting model.…”
Section: Grand Challenge Research Statementsmentioning
confidence: 99%